PENGGUNAAN INFORMASI AKUNTANSI PADA INDUSTRI USAHA KECIL DAN MENENGAH PADA MASA PANDEMI COVID - 19 - Siregar, Mardiana; Sari, Emi Ratna; Rambe, Bhakti Helvi; Prayoga, Yudi (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2021)
The results of this study are to analyze the factors that influence the use of accounting information in the Small and Medium Enterprises Industry in labuhanbatu done by processing statistical data in the form of descriptive statistical processing, normality testing, multiple linear regression. Simultaneous test (F test), partial test (T test) and determination coefficient test with data as many as 33 small and medium business industry players, the data obtained from the R Square Test Result is 0.515 means the independent variable is x1 Leadership Period x2 Education Level, x3 Accounting training simultaneously affects the use of accounting information by 51.5% and the remaining 48.5% is influenced by other factors. Partially, the lead period has a significant effect on the use of accounting information. withthe value of Sig. Leadership Period 0.009 <0.05 has a significant and significant effect on the Use of Accounting Information, so the hypothesis is accepted. Level of educationhas a positive and significant impact on the Use of Accounting Information. As per data onthe value of Sig. Education level 0.008 <0.05 has a significant effect on the use of accounting information. Hence the hypothesisThe variable level of education has a positive effect on the use of accounting information in the Small and Medium Enterprises Industry. Accounting training has a positive and significant effect on the use of accounting information.the value of Sig. Accounting training 0.008 <0.05 has a significant effect on the use of accounting information in the small and medium enterprises industry. Hence the hypothesisAccounting training variables have a positive effect on the use of accounting information in the Small and Medium Enterprises Industry. Simultaneously significant. Where the probability value (Sig.) Is 0.008 <0.05, then the influence of the free variable consists of the Leadership Period variable x1, the Education Level variable x2, the Accounting Training Variable x3 on the dependent variable, the use of accounting information Y in the Small and Medium Business Industry